Management of Traumatic Intracranial Hemorrhage on Anticoagulant Regiment: A Literature Review - Apriawan, Tedy; Kartosen, Ade Anugrah; Ishlahy, Ahmad Z. S.; Broto, Endang Pati; Herjuna, Hana Ranu; Permana, Khrisna Rangga; Meizikri, Rizki; Drehem, Shaleh; Bajamal, Abdul Hafid (Jurnal Medis Islam Internasional, 2020)
Oral anticoagulant and antiplatelet are often prescribed in clinical practice. These drugs are mainly consumed by geriatric patients to prevent or treat cerebrovascular, systemic embolism, or heart condition.  Managing anticoagulated TBI patients is a challenging task for surgeons. This study aims to review available literatures regarding anticoagulated TBI patients and to suggest a treatment algorithm for such cases. Based on several retrospective and prospective studies, it might be wasteful to do a routine follow-up CT scan on anticoagulated TBI patients. The risk of new lesion development or presenting lesion progression seems to be especially low among patients with negative initial CT scan. We suggest to reserve repeat CT scan for patients with evident neurological deterioration. Tighter observation for anticoagulated patients with positive initial CT scan might be useful. Anticoagulation reversal is recommended by the American College of Cardiology, but some studies reported that reversal should be directed by INR. Acute antiplatelet cessation is still controversial for aspirin, but it is advised for clopidogrel. Preoperative management of both anticoagulant and antiplatelet should take into account the bleeding risk of the surgical procedure. Blind cessation and reversal of anticoagulant and/or antiplatelet might delay the timing of surgery and thus would better be avoided